The microscopic features of (Li0.5La0.5)TiO3 - Chung, HT; Cheong, DS (ELSEVIER SCIENCE BV, 1999)
In ionic conducting materials, the crystal structure is closely related to the ionic conductivity. In this research we studied the microscopic features of Li0.5La0.5TiO3 which exhibited a lithium ionic conductivity as high as 1 x 10(-3) Scm(-1) at room temperature by XRD, TEM and SIMS. It was found that the superstructure was caused by the ordering of La+3 and vacancy, producing the 2a(p) x 2a(p) x 2a(p) unit cell. This ordering was found to be regular in microscopic region, but became irregular in macroscopic region. Li+ showed a random distribution which meet the needs for the fast ionic conduction. The second phase was found to be Li2TiO3 which existed in the grain boundary junctions. (C) 1999 Published by Elsevier Science B.V. All rights reserved.
Keywords: LITHIUM ION CONDUCTIVITY; CRYSTAL-CHEMISTRY; PEROVSKITE; TITANATE